Association of Myopia and Genetic Variants of TGFB2-AS1 and TGFBR1 in the TGF-β Signaling Pathway: A Longitudinal Study in Chinese School-Aged Children - Liu, Linjie; He, Juan; Lu, Xiaoyan; Yuan, Yimin; Jiang, Dandan; Xiao, Haishao; Lin, Shudan; Xu, Liangde; Chen, Yanyan (Frontiers in Cell and Developmental Biology, 2021)
Background: Myopia is a complex multifactorial condition which involves several overlapping signaling pathways mediated by distinct genes. This prospective cohort study evaluated the association of two genetic variants in the TGF-β signaling pathway with the onset and progression of myopia and ocular biometric parameters in Chinese school-aged children. Methods: A total of 556 second grade children were examined and followed up for 3.5 years. Noncycloplegic refraction and ocular biometric parameters were measured annually. Multivariate regression analysis was used to assess the effect of the TGFBR1 rs10760673 and TGFB2-AS1 rs7550232 variants on the occurrence and progression of myopia. A 10,000 permutations test was used to correct for multiple testing. Functional annotation of single nucleotide polymorphisms (SNPs) was performed using RegulomeDB, HaploReg, and rVarBase. Results: A total of 448 children were included in the analysis. After adjustments for gender, age, near work time and outdoor time with 10,000 permutations, the results indicated that the C allele and the AC or CC genotypes of rs7550232 adjacent to TGFB2-AS1 were associated with a significantly increased risk of the onset of myopia in two genetic models (additive: P’ = 0.022; dominant: P’ = 0.025). Additionally, the A allele and the AA or AG genotypes of rs10760673 of TGFBR1 were associated with a significant myopic shift (additive: P’ = 0.008; dominant: P’ = 0.028; recessive: P’ = 0.027). Furthermore, rs10760673 was associated with an increase in axial length (AL) (P’ = 0.013, β = 0.03) and a change in the ratio of AL to the corneal radius of curvature (AL/CRC) (P’ = 0.031, β = 0.003). Analysis using RegulomeDB, HaploReg, and rVarBase indicated that rs7550232 is likely to affect transcription factor binding, any motif, DNase footprint and DNase peak. Conclusions: The present study indicated that rs10760673 and rs7550232 may represent susceptibility loci for the progression and onset of myopia, respectively, in school-aged children. Associations of the variants of the TGFBR1 and TGFB2-AS1 genes with myopia may be mediated by the TGF-β signaling pathway; this hypothesis requires validation in functional studies. This trial was registered as ChiCTR1900020584 at www.Chictr.org.cn.